2017
DOI: 10.1007/s00426-017-0928-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trying ‘not to move’ instruction on cortical load and concurrent cognitive performance

Abstract: Motor and cognitive tasks often interfere when performed concurrently. The amount of interference typically scales with difficulty of the tasks involved. Thus, supposedly 'easy' motor tasks with restricted movement amplitude, like sitting on a chair, should show little or no interference with cognitive tasks at all. We measured the processing load induced by different postural tasks and their effect on cognitive performance under cognitive-motor dual-task conditions. Sixteen subjects performed postural motor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Due to the lack of empirical findings on behavioral sex differences in multitasking, it is not surprising that even less is known about their potential neuronal mechanisms. It is fairly established that serial multitasking draws especially on the rostral prefrontal cortex as evidenced by lesion studies (Dreher, Koechlin, Tierney, & Grafman, 2008; Roca et al 2011; Burgess, Veitch, de Lacy Costello, & Shallice, 2000) or functional near-infrared spectroscopy (Langhanns & Müller, 2018). Concurrent multitasking has been linked to areas within the prefrontal cortex, but also parietal, temporal, occipital and cingulate areas in a training study with healthy individuals (Takeuchi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of empirical findings on behavioral sex differences in multitasking, it is not surprising that even less is known about their potential neuronal mechanisms. It is fairly established that serial multitasking draws especially on the rostral prefrontal cortex as evidenced by lesion studies (Dreher, Koechlin, Tierney, & Grafman, 2008; Roca et al 2011; Burgess, Veitch, de Lacy Costello, & Shallice, 2000) or functional near-infrared spectroscopy (Langhanns & Müller, 2018). Concurrent multitasking has been linked to areas within the prefrontal cortex, but also parietal, temporal, occipital and cingulate areas in a training study with healthy individuals (Takeuchi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…High cognitive demand was reflected by large variance of the set point of the position (e.g., center of pressure) and the actual value of the position. However, a recent study revealed that maintaining a seated posture while performing a cognitive task caused the largest decrements in the cognitive task -compared to relaxed lying and slight movement (Langhanns & Müller, 2018). In a study with children (Igarashi et al, 2016), maintaining the seated posture was degraded when accompanied by a concurrent demanding cognitive task.…”
Section: Seated Posturementioning
confidence: 95%
“…Furthermore, several studies have demonstrated that the control and regulation of simple postural tasks such as still sitting require attention. Langhanns and Müller (2018) reported the largest decrements in the cognitive task, while concurrently performing still sitting compared to relaxed lying and slight movement. Igarashi et al (2016) observed the detrimental effect of the regulation of postural control while children concurrently performing difficult cognitive tasks.…”
Section: Association Of Task Difficulty and Distance To The Screenmentioning
confidence: 97%
See 1 more Smart Citation
“…The amount of interference one task has on another scales with the complexity and novelty of the tasks involved. For example, Langhanns and Müller (2017) demonstrated that an instruction to “stay stock-still” during a calculation task required more cortical processing than performing the same cognitive task while sitting or lying down at rest. The explicit instruction to restrict all movement, although not motorically complex, increased the novelty of the sitting task and, therefore, required more cognitive effort for the participants.…”
Section: Clinical Considerations Of Dual Task Performance In Ndmentioning
confidence: 99%